Resistant invasive Candida auris reported in neutropenic patients treated successfully with three antifungals (Indian Journal of Case Reports, 2022)
Candida auris is a deadly fungal pathogen able to cause fatal symptoms in immunocompromised patients. It may be misidentified and difficult to clinically diagnose. The guidelines are to employ Echinocandin and Amphotericin B in the treatment, but the following study elucidates successful treatment of infection by a combination of three classes of antifungal drugs; never reported before. We present a patient with fulminant acute disseminated encephalomyelitis and neutropenia who developed invasive candidiasis despite appropriate antifungal therapy. We successfully treated ongoing candidemia with three antifungal drugs which lead to the resolution of fungemia after 18 days of treatment. Isolation, segregation, waste disposal, and deep cleaning technique were also followed as recommended by the Infectious Diseases Society of America guidelines. First report of Candidemia in an immunocompromised patient was successfully treated with three classes of antifungal drugs, IV Micafungin, Amphotericin B, and Posaconazole for nearly 18 days.